Ligand-Assisted Copper-Catalyzed Oxidative Cross-Coupling of Simple Phenols with Formamides for the Synthesis of Carbamates - Reddy, Nagireddy Veera; Kumar, Gadde Sathish; Kumar, Pailla Santhosh; Kantam, M. Lakshmi; Reddy, Kallu Rajender (Synlett, 2014)
An oxidative approach for the synthesis of phenyl carbamates has been achieved by ligand-assisted copper-catalyzed cross-dehydrogenative coupling (CDC) of phenols with formamides. The direct coupling of simple phenols with mono- and dialkyl formamides provides carbamate products in moderate to good yields under mild reaction conditions.
Keywords: oxidation; formamide; carbamate; copper acetate; coupling reaction